Mapa de unidades geomorfológicas de la cuenca de Loja - Cueva Romero, Génesis Carolina (2015)
The final project involves titration mapping of geomorphological basin Loja to 1:10 000. which was used aerial photos scale 1:30 000 from IGM 1986, geological maps, topographic and land use at different scales. The geomorphological mapping was obtained using photointerpretation techniques where geomorphological units are characterized based on their genesis, morphology and morphometry. The end result was obtained by georeferencing and digitizing aerial photos, with subsequent identification of each geomorphological unit. Depositional, denudativo, structural and tectonic erosion, with the largest presence in the study area: 108 final result geomorphological units classified as genetic unit identified